An evaluation of parameters tuning methods in metaheuristic algorithms - Wong, Kuan Yew, author; Robiah Ahmad, author; Komarudin, author; Regional Conference on Engineering Mathematics, Mechanics, Manufacturing & Architecture (EM ARC) (2007: Putrajaya) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL